CARVING SUPERIOR ACHIEVEMENTS THROUGH INNOVATIVE STRATEGIES IN IMPLEMENTING STUDENTS' CREATIVITY - Istiqomah, Nurul (Managere: Indonesian Journal of Educational Management, 2023)
The Development of Creativity-Innovation in Art Education is a learning achievement that is fun, unique, creative, innovative, and democratic initiative (MUKIDI) and the harmony of learning elements that can increase creativity-innovative in art education. The goals of an effective innovative strategy can encourage student creativity, enable students to explore their interests, and talents, provide space for creative exploration, support the development of critical thinking skills, enrich student learning experiences, stimulate student imagination, support creative education and student achievement and know the high level of achievement that has been achieved, student.The research method used was a qualitative method along with sampling from schools RA Darus Salam and using several data collection techniques, including Library Studies Literature study is a data collection technique that is carried out employing research on library literature. So this research concludes that the use of innovative strategies in education within schools RA Darus Salam can open wider opportunities for students to develop creativity to increase their motivation to achieve high achievements. The implication of these findings is the need for changes in the education system that are more supportive of innovation and creativity, by involving all students in schools RA Darus Salam who have an interest in creating a learning environment that stimulates and motivates students to reach their maximum potential in achieving high achievements. Extraordinary.